ON THE NECESSITY OF FORMING AN ERGONOMIC CULTURE OF FUTURE TEACHERS - Okulova, Larisa (Revista Inclusiones, 2020)
The article considers the problem of the formation of an ergonomic culture with the aim of creating a safe and comfortable educational environment for the development of personality, and maintaining the health of the subjects of the educational process. The presented basis of pedagogical ergonomics provides the development of the need for future teachers to master ergonomic knowledge, skills. The problem of the formation of an ergonomic culture is revealed through the fulfillment of labor functions by future teachers of the modern school as the main condition for the teacher’s professional activity. The ergonomic and pedagogical validity of the effectiveness of the implementation of the labor functions of future teachers in the practice of a modern school, confirmed by empirical research, is given.